The contribution of reflective thinking to the professional development of pre-service teachers. Issue 4 (4th July 2019) - Shavit, Pnina; Moshe, Anat
ABSTRACT: Reflective thinking is an important facet of meta-cognitive thinking. Studies show that reflective journals help students consolidate and assess their practices. The aim of this study was to characterize the reflective thinking process over two years of pre-service teachers in their practical work. Statements from reflective journals, written in each of their practical years, were analyzed by a mixed method approach. 10 pre-service teachers' dairies, in each of their tow practical years was collected, overall 100 reflection were angelized. Statements were sorted; the themes noted were planning, implementation, emotional considerations, and insights. Research Findings strongly indicated, students in their second year of practical teaching focused more on the aspect of personal processes and emotional aspects rather than technical aspects, likely the result of experience garnered during their first year of practice. In both years, it was apparent that reflective writing led students to increased self-awareness.